الوعي بدور الاقتصاد الأخضر في التنمية المستدامة في الجامعات المصرية: دراسة ميدانية على جامعة الإسكندرية - أحمد، تامر سعيد (جامعة الإسكندرية - كلية التربية, 2022)
تتمثل مشكلة البحث في الاقتصاد الأخضر وأثره على التنمية المستدامة التي تتأثر بزيادة الانبعاثات الكربونية الناتجة عن الصناعات القائمة على مصادر الطاقة الغير متجددة والمتمثلة في الفحم والبترول والوقود الحفري مما أدي إلى زيادة الأثار الكربونية الضارة وأيضا تهديد لهذه الموارد التي تتميز بالندرة بالنفاذ قريبا، وتتحقق الدراسة الراهنة من وجود وعي حقيقي بالجامعات بأهمية الاقتصاد الأخضر في تحقيق التنمية المستدامة سواء بين أعضاء هيئة التدريس أو الطلاب، وهل تهتم الجامعة بتحقيق هذا الوعي متضمناً في مناهجها النظرية والعملية، وما هي السبل لتنمية هذا الوعي. ولقد تم الاستعانة بالإجراءات المنهجية الخاصة بالبحوث الوصفية، بالنسبة لأدوات البحث الاجتماعي المناسبة لتحقيق أهداف الدراسة تم الاستعانة بطريقة المسح الاجتماعي بالعينة وتكونت العينة من ٤٠٠ مفردة (٣٠٠ من الطلبة بجامعة الإسكندرية و١٠٠ من أعضاء هيئة التدريس بجامعة الإسكندرية) وتم اختيار الاستبيان كأداة لجمع البيانات ومن أهم نتائج الدراسة ١-إن مناهج جامعة الإسكندرية اهتمت بتوفير نشاطات منهجية تحافظ على بيئة نظيفة وتؤكد على ترشيد استخدام الطاقة والحفاظ عليها وحسن استثمارها وتشجع طلبتها على التقييم الاقتصادي لتقنيات الحفاظ على الطاقة. ٢-إن مناهج جامعة الإسكندرية لم تهتم بدرجة كافية بتحقيق وسائل اتصال فاعلة بطلبتها ومؤسسات المجتمع ولم تعمل بشكل كافي على تحقيق الشراكات مع المجتمع المدني لتطوير خبرات طلبتها بما ينسجم مع حاجات البيئة ٣-إن مناهج جامعة الإسكندرية لم تؤكد بصورة كافية على رؤية الاستدامة وإدارة المشاريع وقلة الدقة والوضوح في نقل المعلومات البيئية إلى الطلبة وبالتالي عدم ارتقاء ترسيخ أخلاقيات المهنة لدى طلبتها إلى درجة مرتفعة بما يحقق بيئة نظيفة. ٤-إن طلبة جامعة الإسكندرية يساهمون في نشاطات لحماية البيئة الخضراء بالجامعة وما حولها وكذلك حملات تنظيف الشوارع داخل الحرم الجامعي وأن معالجتهم لموضوعات تدعم الحفاظ على الثروات البيئية وإجراء الأبحاث ومراجعة المصادر والمراجع المكتبية للمواضيع المتعلقة بالبيئة. 5-أعضاء هيئة التدريس يرون بأن الطلبة لا يمتلكون الوعي البيئي العالي من خلال ممارساتهم البيئية داخل الحرم الجامعي وخارجه للارتقاء للمستوى المطلوب وانهم قد يحتاجون لموضوعات بيئية تدعم الحفاظ على الثروات البيئية أو إقامة حملات توعوية لهم داخل الجامعة للحفاظ على البيئة. The research problem is represented in the green economy and its impact on sustainable development, which is affected by the increase in carbon emissions resulting from industries based on non-renewable energy sources, represented in coal, petroleum and fossil fuels, which led to an increase in harmful carbon effects and also a threat to these scarce resources that will soon run out. Is there a real awareness in universities of the importance of the green economy in achieving sustainable development, whether among faculty members or students, and whether the university is interested in achieving this awareness, including in its theoretical and practical curricula, and what are the ways to develop this awareness. The methodological procedures for descriptive research were used. For the appropriate social research tools to achieve the objectives of the study, the sample social survey method was used. The sample consisted of 400 items (300 students at Alexandria University and 100 faculty members at Alexandria University). The questionnaire was chosen as a tool for data collection and among the most important results the study 1-The curricula of Alexandria University are concerned with providing systematic activities that maintain a clean environment, emphasize the rationalization of energy use, conservation and good investment, and encourage its students to economic evaluation of energy conservation techniques. 2- The curricula of Alexandria University did not pay enough attention to achieving effective means of communication for its students and community institutions, and did not work enough to achieve partnerships with civil society to develop the experiences of its students in line with the needs of the environment 3-The curricula of Alexandria University did not sufficiently emphasize the vision of sustainability and project management, and the lack of accuracy and clarity in conveying environmental information to students, and consequently, the consolidation of professional ethics among its students did not rise to a high degree in order to achieve a clean environment. 4- Alexandria University students participate in activities to protect the green environment at the university and its surroundings, as well as street cleaning campaigns inside the university campus, and that their treatment of topics that support the preservation of environmental wealth, conducting research, and reviewing sources and library references for issues related to the environment. 5- Faculty members believe that students do not have high environmental awareness through their environmental practices inside and outside the university campus to rise to the required level, and that they may need environmental issues that support the preservation of environmental wealth or establish awareness campaigns for them inside the university to preserve the environment.
Keywords: التنمية المستدامة -- الاقتصاد الأخضر -- الجامعات المصرية -- المناهج الدراسية